Synthesis of the reported structure of homocereulide and its vacuolation assay. Issue 5 (1st March 2019) - Naka, Toshihito; Hattori, Yoshihide; Takenaka, Hiroshi; Ohta, Yoichiro; Kirihata, Mitsunori; Tanimori, Shinji
Graphical abstract: Abstract: Homocereulide, isolated from marine bacterium Bacillus cereus, is an analog of emetic toxin cereulide. There is no report on its structure determination and involvement in B. cereus -associated food poisoning. Homocereulide is a cyclic dodecadepsipeptide composed ofl - O -Val-l -Val-d - O -Leu-d -Ala andl - O - allo -Ile-d -Val-d - O -Leu-d -Ala. Here, we synthesized homocereulide using liquid phase fragment condensation. The NMR spectrum of synthesized homocereulide confirmed the intended structure and LC-MS results were consistent with natural products. Morphological evaluation using HEp-2 cells showed higher toxicity with homocereulide (1.39 nM) than cereulide (3.95 nM). Though cereulide is the main component in broth culture, homocereulide is also likely involved in B. cereus -associated food poisoning.